Modulation of Medium-Chain Fatty Acid Synthesis in Synechococcus sp. PCC 7002 by Replacing FabH with a Chaetoceros Ketoacyl-ACP Synthase - Gu, Huiya; Jinkerson, Robert E.; Davies, Fiona K.; Sisson, Lyle A.; Schneider, Philip E.; Posewitz, Matthew C. (Frontiers in Plant Science, 2016)
The isolation or engineering of algal cells synthesizing high levels of medium-chain fatty acids (MCFAs) is attractive to mitigate the high clouding point of longer chain fatty acids in algal based biodiesel. To develop a more informed understanding of MCFA synthesis is photosynthetic microorganisms, we isolated several algae from Great Salt Lake and screened this collection for MCFA accumulation to identify strains naturally accumulating high levels of MCFA. A diatom, Chaetoceros sp. GSL56, accumulated particularly high levels of C14 (up to 40%), with the majority of C14 fatty acids (~2/3) allocated in triacylglycerols. Using whole cell transcriptome sequencing and de novo assembly, putative genes encoding fatty acid synthesis enzymes were identified. Enzymes from this Chaetoceros sp. were expressed in the cyanobacterium Synechococcus sp. PCC 7002 to validate gene function and to determine whether eukaryotic enzymes lacking bacteria evolutionary control mechanisms could be used to improve MCFA production in this promising production strains. Replacement of the Synechococcus 7002 native FabH with a Chaetoceros ketoacyl-ACP synthase III increased MCFA synthesis up to five fold. The level of increase is dependent on promoter strength and culturing conditions.